Ефективність управління потенціалом виробничої потужності сервісних підприємств з урахуванням мотивації клієнтів - Субочев, Олександр Іванович; Subochev, Oleksandr; Січко, Олександр Михайлович; Sichko, Olexander; Погорєлов, Михайло Григорович; Pogorelov, Mihaylo; Коваленко, Ігор; Kovalenko, Igor; Гаврон, Надія; Havron, Nadiia (Ternopil Ivan Puluj National Technical University, Ternopil, 2019)
Розроблено методику аналізу виробничої діяльності постів, що дозволяє виявляти клієнтів за їх категоріями і територіальної "прихильності'', поява яких слід активізувати конкретному сервісному підприємству. Розроблено алгоритм пошуку рішень щодо поліпшення якості послуг та умов обслуговування клієнтів автосервісу. Виконана практична реалізація методики на базі діючих сервісних підприємств з обслуговування вантажних автомобілів. Виявлено заходи щодо збільшення потенціалу виробничої потужності сервісних підприємств, що дозволяє конкретному підприємству підтримувати свою економічну стабільність в умовах конкуренції.A methodology has been developed for analyzing the production activities of posts, which allows identifying customers by their categories and territorial "affections", the emergence of which should be activated by a specific service enterprise. An algorithm has been developed for finding solutions for improving the quality of services and customer service conditions for a car service center. The practical implementation of the methodology was carried out on the basis of existing service enterprises for servicing trucks. Were found measures to increase the capacity of the production capacity of service enterprises, allows a particular enterprise to maintain its economic stability in a competitive environment. The criteria reflecting the production activities of the auto service enterprise are selected and justified. It is established that regular customers who apply for services more than three times, bring more revenue.
Efficiency of managing the production capacity of service enterprises, taking into account customer motivation
Keywords: сервісне підприємство; Service enterprise; виробнича діяльність; production activity; клієнт; customer; якість послуг; quality of services